Glycogen Turnover Forms Lactate during Exercise - Shulman, R. G. (Exercise and Sport Sciences Reviews, 2005)
The power needs of muscle are supplied by rapid anaerobic glycogenolytic ATP generation. Lactate is built up by the mismatch between steady state energy needs and short-term power demands and the increased concentration drives the lactate shuttle. In this model, contributions to fatigue should be looked for in the flux of glucose through glycogen rather than in the concentrations of fuel.